2018
DOI: 10.1177/0731948718768512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Student Choice of Instructional Method on the Learning Outcomes of Students With Comorbid Learning and Emotional/Behavioral Disabilities

Abstract: Within the Individuals With Disabilities Education Act (IDEA) of 2004, the federal definition of learning disabilities (LD) excludes learning problems that are primarily the result of emotional and behavioral disabilities (EBD). However, students identified as having LD demonstrate a high incidence of concurrent internalizing and externalizing behavioral problems. The National Center for Learning Disabilities report, "The State of Learning Disabilities: Facts, Trends, and Emerging Issues" (Cortiella & Horowitz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
(54 reference statements)
0
15
0
1
Order By: Relevance
“…As students with learning disabilities move from one stage to the next, academic requirements and expectations also increase. This is particularly true because evidence shows that learning disabilities have divergent characteristics (Billingsley et al, 2018), while more has to be researched on instructional practices enhancing learning outcomes, achievement and level of engagement of students with learning disabilities (Billingsley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As students with learning disabilities move from one stage to the next, academic requirements and expectations also increase. This is particularly true because evidence shows that learning disabilities have divergent characteristics (Billingsley et al, 2018), while more has to be researched on instructional practices enhancing learning outcomes, achievement and level of engagement of students with learning disabilities (Billingsley et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Before doing so, the teacher gave descriptions, then invited the students to be active by giving the case result which was discussed or guessing the information requested. Billingsley, Thomas, & Webber (2018) investigated the effects of direct teaching, computer-assisted instruction (CAI), and a combination of both.The study showed the unique contributions of direct teaching and CAI toward the secondary mathematics learning; however, not all the Direct Instruction lessons began with skill descriptions as some the Direct Instruction lessons did not involve skills. Davis' research (2018) on the interpretation of direct instructions revealed a variety of class phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when students with SLD have problems writing, accommodations may include dictating responses or using text‐to‐speech technology (Young et al., 2019). For other students with SLD who are experiencing difficulties with math calculations when solving word problems (Billingsley et al., 2018), calculators may be among the accommodations included in their IEPs.…”
Section: High School Students With Learning Disabilities: Requesting Accommodations In Role‐playmentioning
confidence: 99%